B-cell-related biomarkers of tolerance are up-regulated in rejection-free kidney transplant recipients - Viklicky, Ondrej; Krystufkova, Eva; Brabcova, Irena; Sekerkova, Alena; Wohlfahrt, Peter; Hribova, Petra; Wohlfahrtova, Mariana; Sawitzki, Birgit; Slatinska, Janka; Striz, Ilja; Volk, Hans-Dieter; Reinke, Petra (Transplantation, 2013)
BACKGROUND: Molecular signatures have recently been identified in operationally tolerant long-term kidney transplant patients; however, their expression in patients on immunosuppression remains unclear. METHODS: In this prospective study, the gene expression profiles of eight selected tolerance-associated genes (MS4A1, CD79B, TCL1A, TMEM176B, FOXP3, TOAG-1, MAN1A1, and TLR5) in the peripheral blood of 67 kidney transplant recipients at days 0, 7, 14, 21, 28, 60, 90, and at 6 and 12 months, and in graft biopsies were measured. Similarly, using flow cytometry, CD45CD19CD3 B-cell counts were evaluated in the follow-up. Expression patterns were compared among patients with biopsy-proven acute rejection, borderline changes, and in rejection-free patients. A generalized linear mixed model with gamma distribution for repeated measures adjusted for induction therapy was used for statistical analysis of longitudinal data and Kruskal-Wallis test for case biopsy data. RESULTS: Compared to patients with rejection, a significantly higher number of peripheral B cells were observed during follow-up in rejection-free patients and in patients with borderline changes. Gene expression patterns of MS4A1 (CD20), TCL1A, CD79B, TOAG-1, and FOXP3 genes were significantly higher in rejection-free patients as compared to rejection group with the highest differences during the first 3 months. In contrast, TMEM176B (TORID) was up-regulated in the rejection group. Similar trends were also observed between patients with borderline changes and acute rejection. Higher intragraft expression of TOAG-1 was observed in rejection-free patients. CONCLUSIONS: These observations suggest an association of B-cell signatures, seen also in drug-free tolerant patients, with controlled alloimmune response.
Keywords: Forkhead Transcription Factors; upregulace; Humans; Up-Regulation; lidé středního věku; forkhead transkripční faktory; Graft Rejection; Female; Aged; Immune Tolerance; dospělí; senioři; lidé; Biomarkers; B-lymfocyty; protoonkogenní proteiny; Adult; transplantace ledvin; biologické markery; ženské pohlaví; Male; Middle Aged; B-Lymphocytes; stanovení celkové genové exprese; imunologická tolerance; Proto-Oncogene Proteins; Kidney Transplantation; Gene Expression Profiling; mužské pohlaví; prospektivní studie; rejekce štěpu; Prospective Studies